Bone conduction implants – a rapidly developing field. Issue 10 (7th September 2015) - Edmiston, R C; Aggarwal, R; Green, K M J
Abstract: Background: Since their introduction in 1977, the technology and surgical techniques surrounding the use and application of bone-anchored hearing devices have developed considerably. Objective: This article reviews current developments in the use of bone-anchored hearing devices, looking at the possible options for patients, complications encountered and future possibilities. Conclusion: Advances in surgical technique are described, with the move towards the use of linear incisions and no soft tissue reduction. Methods for preventing complications are analysed, with review of different abutments and the introduction of the active bone conduction implant.